MEMANFAATKAN MARKETPLACE SEBAGAI MEDIA PROMOSI UNTUK MENINGKATKAN PENJUALAN DI TENGAH PANDEMI COVID-19 - Agus Dwi Cahya; Fadhilla Ajeng Aqdella; Asfarina Zahrotul Jannah; Hesthi Setyawati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
This research examines the company's strategy to survive the product by using promotional media to increase sales in the midst of a pandemic by using the marketplace as a promotional medium. With the development of internet technology, the way of transacting and promoting changes. Transaction and promotion processes are carried out by utilizing internet media, one of which is using E-commerce E-commerce is a process of buying and selling through internet media that is able to streamline time, one of which is to improve the promotion process. The role of e-commerce has a positive impact, one of which is to increase the promotion process. Some of the e-commerce platforms that support are Lazada, Shopee. and Tokopedia. The method in this research is using descriptive qualitative method with the object of research is UMKM Jaka. On the other hand, the massive use of digital marketing has been made to increase sales in the marketplace. Marketplace as a manifestation of e-commerce is used as an innovation or change in sales methods. This research reveals that during the pandemic, consumers almost forgot about the brand, so the most appropriate communication promotion media to increase sales is through the marketplace. Digital behavior is driving the expansion of online consumers to increase sales amid the pandemic.